Peran Guru sebagai Fasilitator dalam Pengelolaan Kelas Konstruktivis: Studi Kasus pada Mahasiswa Program Studi Pendidikan Bahasa Inggris - Harputra, Yuswin; Tambunan, Elissa Evawani (ETANIC Journal Of English Language Teaching And Applied Linguistics, 2024)
This study aims to evaluate the role of facilitators in managing constructivist classrooms among English Education students and to analyze the practices and challenges encountered in implementing this approach. As the constructivist approach in education becomes more prevalent, it is crucial to understand how prospective English teachers perform their roles as facilitators. This research provides relevant insights for the professional development of students and the enhancement of future teaching quality. The study employs a qualitative approach with a case study method. Data were collected through questionnaires distributed to 15 English Education students and direct classroom observations. The questionnaire covered aspects of beliefs, attitudes, and practices in the facilitative role. Analysis was conducted to evaluate students' assessments of their roles, and to identify patterns and challenges in teaching practices. The results indicate that the average rating for teachers' beliefs about their facilitative role is 4.5, with student interaction receiving the highest rating (4.8). Although there is strong belief in the effectiveness of constructivist learning, some teachers remain neutral regarding its comparison with traditional teaching methods. In practice, many teachers use problem-based projects (average rating 4.0) and support active student participation in discussions (average rating 4.6). Technology use in teaching remains uneven (average rating 4.1), and there is room for improvement in providing in-depth and constructive feedback (average rating 4.5). The study identifies challenges such as time constraints, variability in student abilities, and access to technology, and provides recommendations for further training and support for teachers to enhance the implementation of constructivist approaches in the classroom.